2016
DOI: 10.3390/ijerph13111145
|View full text |Cite
|
Sign up to set email alerts
|

Semiparametric Multinomial Ordinal Model to Analyze Spatial Patterns of Child Birth Weight in Nigeria

Abstract: Abstract:Background: Birth weight is an important health parameter for obstetricians and gynaecologists. It is a good health indicator of a child-bearing mother and a strong predictor of infant morbidity and mortality. Methods: This paper utilizes data on 28,647 children born between 2003-2008 obtained from the 2008 Nigeria Demographic and Health Survey (NDHS). For a simple epidemiological convenience, the occurrence of a newborn weight can intuitively be considered to be categorical in nature and the threshol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…When the resulted variable is polychotomous, it can happen in a variety of ways. Multinomial and ordinal outcome variables are two types of outcome variables (Fahrmeir and Lang 2001 ; Rasheed et al, 2016 ). The multinomial logistic regression model cannot be used when the dependent variable is categorized by order of magnitude.…”
Section: Materials and Methodologymentioning
confidence: 99%
“…When the resulted variable is polychotomous, it can happen in a variety of ways. Multinomial and ordinal outcome variables are two types of outcome variables (Fahrmeir and Lang 2001 ; Rasheed et al, 2016 ). The multinomial logistic regression model cannot be used when the dependent variable is categorized by order of magnitude.…”
Section: Materials and Methodologymentioning
confidence: 99%
“…However, only a limited number of studies from Africa were included in the meta-analyses [ 4 , 7 , 11 , 12 ], a region with a high burden of LBW [ 10 ], and predominant use of polluting fuels [ 1 ]. The studies from Africa were limited to relatively few countries, including Ghana [ 13 ], Nigeria [ 14 , 15 , 16 , 17 ], Malawi [ 18 ], Ethiopia [ 19 , 20 , 21 ], and Zimbabwe [ 22 ]. The African studies were limited to hospital-based settings [ 21 ] with a reliance on the woman’s subjective recall of the birth weight or size of the child [ 14 , 18 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The studies from Africa were limited to relatively few countries, including Ghana [ 13 ], Nigeria [ 14 , 15 , 16 , 17 ], Malawi [ 18 ], Ethiopia [ 19 , 20 , 21 ], and Zimbabwe [ 22 ]. The African studies were limited to hospital-based settings [ 21 ] with a reliance on the woman’s subjective recall of the birth weight or size of the child [ 14 , 18 , 22 ]. The studies did not address the effect of outdoor or indoor place of cooking on LBW risk [ 13 , 14 , 15 , 17 , 23 ], or generally control for important confounders [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several LBW studies related to the development of statistical models have been carried out, such as the classification of LBW with a nonparametric approach using the Weighted Probabilistic Neural Network method (Yasin & Ispriyansti, 2017), and analysis of risk factors for LBW cases using LASSO and Fused LASSO selection techniques (Kurniawati et al, 2020). Besides, Khan et al (2018) also identified LBW in Bangladesh using a mixed logistic model and Adeyemi et al (2016) developed a spatial effect on the LBW model in Nigeria using a semiparametric multinomial ordinal model. Risk factors that affect the birth size of a baby can be analyzed by using the POM and NPOM models.…”
Section: Introductionmentioning
confidence: 99%